ChemInform Abstract: Ligand‐Free Pd‐Catalyzed C—N Cross‐Coupling/Cyclization Strategy: An Unprecedented Access to 1‐Thienyl Pyrroloquinoxalines (III) for the New Approach Towards Apoptosis. Issue 12 (March 2015) - Kolli, Sunder Kumar; Nakhi, Ali; Archana, Sivakumar; Saridena, Maneesha; Deora, Girdhar Singh; Yellanki, Swapna; Medisetti, Raghavender; Kulkarni, Pushkar; Ramesh Raju, R.; Pal, Manojit
Abstract New compound (IIIe) appears to be a novel apoptotic agent of further interest.